2021
DOI: 10.1186/s12929-021-00736-4
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic approaches of mesenchymal stem cells-derived exosomes

Abstract: Mesenchymal stem cells (MSCs) have been demonstrated to have a great potential in the treatment of several diseases due to their differentiation and immunomodulatory capabilities and their ability to be easily cultured and manipulated. Recent investigations revealed that their therapeutic effect is largely mediated by the secretion of paracrine factors including exosomes. Exosomes reflect biophysical features of MSCs and are considered more effective than MSCs themselves. Alternative approaches based on MSC-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 134 publications
(148 reference statements)
2
49
0
1
Order By: Relevance
“…EVs from various cell types, mainly including mesenchymal stem cells (MSCs), are currently being explored as “cell-free” therapeutic tools and have been extensively studied for their role in stimulating tissue regeneration by conferring proangiogenic, proliferative, anti-apoptotic and anti-inflammatory actions thorough transport of their protein cargo and RNAs [ 119 , 120 ]. The growing number of recent studies also suggests that the regenerative potential of the MSC treatments is mediated by EVs or conditioned medium rather than by cells [ 121 , 122 , 123 , 124 ].…”
Section: Therapeutic Use Of Platelet-derived Extracellular Vesiclesmentioning
confidence: 99%
“…EVs from various cell types, mainly including mesenchymal stem cells (MSCs), are currently being explored as “cell-free” therapeutic tools and have been extensively studied for their role in stimulating tissue regeneration by conferring proangiogenic, proliferative, anti-apoptotic and anti-inflammatory actions thorough transport of their protein cargo and RNAs [ 119 , 120 ]. The growing number of recent studies also suggests that the regenerative potential of the MSC treatments is mediated by EVs or conditioned medium rather than by cells [ 121 , 122 , 123 , 124 ].…”
Section: Therapeutic Use Of Platelet-derived Extracellular Vesiclesmentioning
confidence: 99%
“…However, accumulative evidence has demonstrated that exosomes carry many bioactive molecules including nucleic acids, proteins, lipids, metabolites ( Zhang Y. et al, 2020 ; Kalluri and LeBleu 2020 ). These encapsulated materials are transported to neighboring or distant cells selectively, which contribute to cell-cell communication, signal transduction, immune response modulation, antigen presentation, and epigenetic reprogramming of recipient cells ( Janockova et al, 2021 ). The biological functions of exosomes are heavily dependent on physiological/pathological conditions of originating tissues or cells at the time of exosome secretion, and the surface receptors of the recipient cells ( Alcayaga-Miranda et al, 2016 ).…”
Section: Featured Properties Of Dental Stem Cells and Exosomesmentioning
confidence: 99%
“…Several studies compared the MSC-based versus MSC-EV-based therapies, showing similar outcomes and insignificant differences in therapeutic performance between the two approaches (reviewed in [ 66 , 107 , 108 ]). Visualization of the mouse brains after intranasal delivery of MSCs or MSC-EVs demonstrated that MSC-EVs produced much higher signals of integration into the brain parenchyma than MSCs, both on bioimaging with fluorescent labelling and on immunostaining [ 109 ].…”
Section: Potentials Of Msc-evs As a Cell-free Platform Of Therapeutic Delivery To The Brainmentioning
confidence: 99%